1986
DOI: 10.1177/036354658601400105
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise on anterior-posterior knee laxity

Abstract: A commercial knee laxity testing device was used to quantitate anterior and posterior laxity before and after exercise. Measurements were made at 20 degrees of knee flexion and with a displacement force of 133 N (30 pounds). In sedentary controls no significant change in laxity was noted over 2 hours. Squat power lifters sustained no significant change in laxity after a series of squats (0.4 to 0.7 cm) using 1.6 times body weight. However, 18% to 20% increases in mean anterior and posterior laxity were noted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
49
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 26 publications
6
49
3
Order By: Relevance
“…We found a significant increase in anterior laxity in normal knees after exercise, supporting the results of previous studies (Stoller et al 1983, Skinner et al 1986, Steiner et al 1986). The effects of exercise on knees with ACL grafts demonstrated that the change in the anterior laxity of the reconstructed knees was similar to that in normal knees.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found a significant increase in anterior laxity in normal knees after exercise, supporting the results of previous studies (Stoller et al 1983, Skinner et al 1986, Steiner et al 1986). The effects of exercise on knees with ACL grafts demonstrated that the change in the anterior laxity of the reconstructed knees was similar to that in normal knees.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings suggest that the ACL grafts are biomechanically and biochemically different from normal ACLs, even 15 months after ACL reconstruction. An increase in knee joint laxity after exercise haxDbeen reported by some investigators (Stoller et al 1983, Skinner et al 1986, Steiner et al 1986). This phenomenon was thought to be caused by decreased resting muscle tone due to fatigue, the viscoelastic behavior of the ligaments and other structures surrounding the knee joint, or by an elevation in temperature (Woo et al 1987, Fukubayashi et al 1991.…”
Section: Anterior Laxity and Mr Signals Of The Knee After Exercisementioning
confidence: 70%
“…Stoller et al (1983) reported that torsional knee laxity, with 10-Nm internal and external torque to the tibia, increased by 14% after 30 minutes of running and that it returned to the level before exercise 52 minutes after running. Steiner et al (1986) reported that, in sedentary controls who were mainly sitting, no change in laxity was noted over 2 hours. Squat power lifters showed no change in laxity.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the threshold of exercise that causes the maximum change is low. Acute changes in knee laxity after exercise have been reported by several investigators (Weisman et al 1980, Stoller et al 1983, Skinner et al 1986, Steiner et al 1986, Johannsen et al 1989, Sakai et al 1992. The knee joint is considered to have viscoelastic properties during exercise.…”
Section: Anterior-posterior Knee Laxity Increased By Exercisementioning
confidence: 94%
“…There are reports of increased laxity in normal knees after activities such as running to fatigue:%gility running (23%) ,z6 distance running (20%) ," cycling (21%) ,I2 and basketball (19%) . 35 Pintsaar et a1 suggested that the medial-lateral (frontal plane) component of dynamic postural stability during unilateral stance resembled the adjustments that occur during the unilateral support phases of walking or running. 24 When the ankle and subtalar joints are adequately controlled by neuromuscular forces, they can more efficiently perform effective postural corrections.…”
mentioning
confidence: 99%